Therapy after cyclin‐dependent kinase inhibition in metastatic hormone receptor‐positive breast cancer: Resistance mechanisms and novel treatment strategies. Issue 15 (19th May 2020) - Sharifi, Marina N.; Anandan, Apoorva; Grogan, Patrick; O'Regan, Ruth M.
Abstract : Endocrine therapy has been the standard of care for patients with metastatic hormone receptor (HR)‐positive, HER2‐negative breast cancer since the 1970s, improving survival while avoiding the toxicities associated with cytotoxic chemotherapy. However, all HR‐positive tumors ultimately develop resistance to endocrine therapy. Cyclin‐dependent kinase 4 and 6 (CDK4/6) inhibitors have more recently become an important component of the management of this breast cancer subtype, significantly delaying time to the disease progression and improving survival when combined with endocrine therapy. However, as with endocrine therapy alone, treatment resistance remains a universal phenomenon. As more women receive CDK4/6 inhibitors as part of their treatment, the management of de novo and acquired resistance to combined CDK4/CDK6 inhibitor plus endocrine therapy regimens has emerged as an important clinical challenge. Several resistance mechanisms have been described, including alterations in the CDK4/6/cyclin D complex or its major effector retinoblastoma protein (pRb), bypass signaling through other cyclin/CDK complexes and activation of upstream signaling pathways, in particular the PI3K/mTOR pathway, but robust biomarkers to predict resistance remain elusive, and the role for continuing CDK4/6 inhibitors after progression remains under investigation. Novel strategies being evaluated in clinical trials include the continuation of CDK4/6 inhibitors through progression, as well as triplet therapy combinations with PI3K inhibitors or immune checkpoint inhibitors. Abstract : As more women receive CDK4/6  inhibitors as part of their treatment for metastatic hormone receptor‐positive breast cancer, the management of de novo and acquired resistance to combined CDK4/6 inhibitor plus endocrine therapy regimens has emerged as an important clinical challenge. Novel strategies being evaluated in clinical trials include the continuation of CDK4/CDK6 inhibitors through progression as well as triplet therapy combinations with PI3K inhibitors or immune checkpoint inhibitors.